Normal and self-adjoint composition operators on the space of analytic functions - Mozhyrovska, Z.G. (Carpathian Mathematical Publications, 2009)
We consider spectral properties of normal composition operators and investigate some properties of self-adjoint operators on space of analytic functions on Hilbert space.